Lessons Learnt from financing WASH rehabilitation works in small towns in Zimbabwe. Issue 4 (19th May 2021) - Cole, Arnold; Mudhuviwa, Steve; Maja, Taurai; Cronin, Aidan
ABSTRACT: This paper describes urban WASH interventions (hardware, hygiene promotion, and institutional support) implemented in the Small Towns WASH Programme (STWP) across 14 towns in Zimbabwe with the associated costing. Key lessons in terms of urban WASH rehabilitation include the need for flexible funding and programme approaches accommodate changes during implementation, and that strong programme governance, multi-stakeholder involvement, and integration of hardware and software are required to contribute to benefits beyond infrastructure rehabilitation alone. Critical recommendations for sustaining the rehabilitated infrastructure and institutional strengthening are presented.